Geofencing-Based Real-Time Monitoring System for Endangered Animal Tracking and Protection - Tasha Nadira Abdullah,; Aimi Syamimi Ab Ghafar, (Progress in Engineering Application and Technology, 2026)
This project is to develop a real-time animal tracking and monitoring system to enhance the conservation of endangered species. By integrating Internet of Things (IoT) technology with geofencing and data analytics, the project aims to address the limitations of traditional wildlife monitoring methods that often lack real-time data and structured analysis. The system utilizes a Raspberry Pi 4 microcontroller equipped with a UPS HAT module to ensure uninterrupted operation, a GPS module for location tracking, and an MPU6050 accelerometer and gyroscope sensor for motion detection and behavioural pattern analysis. The systme use Telegram for delivering real-time notifications and monitoring updates, providing a cost-effective and accessible solution that enables conservationists to receive immediate alerts on standard mobile devices without requiring specialized infrastructure. With the implementation of geofencing, automated alerts are triggered via Telegram when animals move beyond designated safe zones or into high-risk areas, enabling rapid response from conservation teams to prevent poaching incidents, human-wildlife conflicts, or other threats. Ultimately, the project seeks to support data-driven decision-making and improve the effectiveness of protection strategies for endangered wildlife through continuous real-time monitoring.